IMPLEMENTASI HYBRID INTELLIGENT INFORMATION SYSTEM UNTUK DIAGNOSIS KEPERAWATAN - Ratih Alfionita; Rosa Delima; Antonius Rachmat C. (Jurnal Informatika, 2014)
By increasing amounts of data, a system gets more complex in accessing and processing, especially if the system is used to process information and makes a decision. Hybrid Intelligent Information System is a combination of information systems and expert systems. The system is better able to process the data and information, that generated be some knowledge to support decision making. Some application needs to process complex and large data, such as Medical Information Systems. Determination of medical treatment provided by nurses on patients can be obtained from the grievances felt by the patient and the history of medical treatment was ever given. Merger between expert systems and information systems are embedded in a computer is expected to facilitate the nurse in providing medical treatment to patients. Certainty Factor method was chosen to implement the expert system. Certainty Factor calculates the level of trust and user response will determine a nursing diagnosis decisions. After analyzing and testing, it was concluded that the Hybrid Intelligent Information System for Nursing Diagnosis can generate nursing diagnoses with 93.796% accuracy of diagnosis in 20 cases of a given expert.